Pengaruh NPL, DPK, dan CAR Terhadap ROA (Studi Pada Bank Non Devisa di Indonesia) - Artha, Bhenu; Ayu Krisna Murti, Desy; Puput Aryanti, Rista (Universitas Bojonegoro, 2021)
This study aims to determine the effect of non-performing loans (NPL), capital adequacy ratio (CAR), and third party funds (TPF) on return on assets (ROA) in non-foreign exchange banks in Indonesia for the period 2010-2016. The results show that TPF variable has a significant positive effect on ROA, while CAR and NPL have no effect on ROA.